A comparative study for determination of thermal inactivation parameters of Salmonella in high gel and standard egg white powder using three methods. (30th December 2022) - Sun, Shengqian; Anderson, Nathan M.; Walker, Lin; Thippareddi, Harshavardha
Abstract: Egg white powder (EWP), the main ingredient in many food products, is widely used in the food industry due to its whipping, textural properties and practical advantages. Significant food safety risks might occur when contamination/cross-contamination takes place after a lethal processing step. It is critical to use appropriate D- and Z-values to evaluate the food safety risks. However, different thermal destructing methods may result in discrepancies in thermal resistance values of the same food matrix. Four isothermal treatments at 75, 80, 85, and 90 °C were studied in EWP using three methods for comparison, thermal death disks water bath (TDWB), plastic bags water bath (PBWB), and plastic bags dry bath (PBDB). D-values for Salmonella under four isothermal temperatures were greater (P < 0.05) in Standard EWP compared to High Gel EWP, respectively; The average Z-values for Salmonella were in the range of 10.62 °C–14.57 °C. D-values resulted significant difference (P < 0.05) using TDWB and PBWB, but no significant difference was observed between PBDB and PBWB. These results can be potentially applied for EWP pasteurization, and PBDB may provid a better way of studying a large variety of powdered products regarding thermal inactivation parameters of pathogens. Highlights: D and Z-values were studied in egg white powder using three thermal treatments. Three methods were compared for the evaluation of Salmonella in Egg White Powder. pH had a significant effect on the Salmonella thermotolerance in Egg White Powder. Plastics bags dry bath provided a more suitable way of studying powdered products.